1990
DOI: 10.1002/j.1460-2075.1990.tb08327.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular transport of cholera toxin B subunit using Neisseria IgA protease beta-domain: conformation-dependent outer membrane translocation.

Abstract: The fl-domain of the Neisseria IgA protease precursor (Iga) provides the essential transport function for the protease across the outer membrane. To investigate the secretion function of the f-domain (Igaf), we engineered hybrid proteins between Iga, and the non-toxic 12 kd cholera toxin B subunit (CtxB) and examined their targeting behaviour in Salmonella typhimurium. We show that CtxB-Igao hybrid proteins integrate into the outer membrane, leading to the exposition of the CtxB moiety on the cell surface. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
0
5

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(181 citation statements)
references
References 45 publications
4
172
0
5
Order By: Relevance
“…However, constructs used in that study preserved a significant portion (Ͼ100 residues) from the C terminus of the wild type passenger, including a segment shown previously to be important for passenger folding and OM translocation (9, 10, 39 -41). In addition, many studies have found the AT secretion process to be severely disrupted under conditions that induced passenger folding in the periplasm (10,24,42,43), consistent with our simulation results. On balance, it appears that AT OM translocation can be severely disrupted either by premature folding in the periplasm or by a disruption of folding at the cell surface, particularly in the C-terminal region of the passenger.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, constructs used in that study preserved a significant portion (Ͼ100 residues) from the C terminus of the wild type passenger, including a segment shown previously to be important for passenger folding and OM translocation (9, 10, 39 -41). In addition, many studies have found the AT secretion process to be severely disrupted under conditions that induced passenger folding in the periplasm (10,24,42,43), consistent with our simulation results. On balance, it appears that AT OM translocation can be severely disrupted either by premature folding in the periplasm or by a disruption of folding at the cell surface, particularly in the C-terminal region of the passenger.…”
Section: Discussionsupporting
confidence: 91%
“…7). Although this has been demonstrated previously for other ATs (23,42,44), the secretion efficiency of a cleavage-deficient mutant has to our knowledge never been tested in the absence of folding. The fact that cleavage could not rescue OM translocation of the folding-impaired 4K pertactin means that cleavage represents a separate process uncoupled from secretion.…”
Section: Discussionmentioning
confidence: 74%
“…The technique is a minor modification of a method by Klauser et al (1990). Round glass coverslips were boiled for 1 min in 0?1 M HCl before storage in 95 % ethanol prior to air-drying for use.…”
Section: Methodsmentioning
confidence: 99%
“…The soluble proform matures further into the functional 106-kDa IgA1 protease and a small stable ␣-protein. It is possible to find the active IgA1 protease in the culture medium from iga-transformed E. coli and S. enterica (185,253), supporting the concept that the IgA1 protease precursor contains all the necessary determinants to direct the translocation of the protease from the periplasm into the medium, without the participation of accessory proteins (401). Since no energy coupling or accessory factor seemed to be required for the translocation process, and unlike the type I to IV systems, the molecules targeted for secretion were strictly dedicated to their covalently linked cognate ␤-domain, the proteins secreted in this fashion received the name of autotransporters.…”
Section: Autotransporter Secretion Pathway (Type Va)mentioning
confidence: 99%